SOLUTIONS IMPACT OF USE OF GADGETS ON SOCIAL BEHAVIOR OF EARLY CHILDREN - Indi Aminah; Elihami Elihami; Masnur Masnur (JURNAL EDUKASI NONFORMAL, 2020)
Research with Non-formal Education Strategies in Overcoming the Impact of Using Gadgets on Social Behavior of Early Children in Kindergarten Pgri Kulinjang, Tuara Village, Enrekang District which aims to find out how forms of early childhood gadget use, impacts and non-formal education strategies in dealing with early childhood gadget use in kindergarten PGRI Kulunjang used a qualitative method where data was taken using direct field observations with research subjects namely the early age pupils of TK PGRI Kulinjang as many as 11 students with a frequency of 5 girls and 6 boys. The use of gadgets in the development of early childhood social behavior in Kindergarten PGRI Kulinjang has both positive and negative impacts on students' daily lives at home and at school. Forms of using gadgets such as playing, watching and learning, the positive impact is that students become creative and have high imagination, train the child's brain power in memorizing and remembering while the negative impact is that the child becomes a closed person. The non-formal education strategy is to Operational funding assistance education, socialization and promotion strategies as well as activity implementation reports.